PERLINDUNGAN HUKUM BAGI KONSUMEN TERHADAP TINDAKAN PENIMBUNAN MASKER AKIBAT DARI PEYEBARAN COVID-19 - Septian Arif Suryanto (2021)
This study discusses issues regarding consumer protection, especially legal protection to consumers as masks purchaser based on Law Number 8 of 1999. It also discusses dispute settlement towards business actors as masks hoarders which is clearly affecting consumers. Researcher implemented the normative juridical research, which used library method by examining various secondary data sources in the form of books, journals, legislation and other legal writings related to research discussion. The results of this study indicate that legal protection for consumers who purchase masks based on Law Number 8 of 1999 is to guarantee and strictly regulate consumer rights and impose obligations on business actors who selling masks in the form of aspect which is allowed and prohibited. The settlement of disputes against business actors who hoard masks that harm consumers are executed through the General Court (litigation)by filing a lawsuit, and also through the Consumer Dispute Settlement Agency (non-litigation) which is carried out by conciliation, mediation, or arbitration.